Data security for internet plus in public cloud - Yongjian WANG; Aibo SONG; Yawei YE; Haibo JIANG (Dianxin kexue)
“Internet plus” has given birth to many new economic forms and business models,the public cloud faces a serious security challenges.The security of public cloud data was studied and the research ideas were put forward.Firstly,the concept of homomorphic encryption,the characteristics of additive homomorphic encryption and multiplicative homomorphic encryption,and the current research results and difficult problems to be solved were analyzed.Then,based on the multiplicative homomorphic encryption algorithm,hash table and similarity theory,a data security protection scheme was proposed,and the concrete realization process was described.The similarity and completeness of the encrypted data in the public cloud were tested by Euclidean distance.Finally,the correctness and security of the scheme were analyzed by theory.The simulation results verify the feasibility and validity of the scheme.